Francouzské pojetí geopolitiky (Czech Journal of International Relations, 2001)
Aymeric Chauprade, Francois Thual: Dictionnaire de Géopolitique. Etats, Concepts, Auteurs. 1.ere edition. Paris: Elipses, 1998, 621 stran, ISBN 2-7298-9857-3. Signatura knihovny ÚMV 47 090.